Spatial and temporal variability in soil physical conditions for root growth: interactions between soil, water and root growth for sustainable agriculture - McKenzie, Blair M. (Agrociencia Uruguay, 2012)
Plants and hence crops grow best when their roots are able to proliferate through soft stable soil. Crops with prolific root systems use water and nutrients efficiently, generally have greater yields and are best placed to resist or minimise disease. For most plants, physical constraints including mechanical impedance, water stress and oxygen deficiency limit root proliferation. However these constraints differ with location in the soil and change with time. Roots may exploit structural cracks and biopores in the soil and by so doing gain access to water and other resources at depth, but to fully exploit the soil resources roots must not be confined to these largest of pores and must explore the soil matrix. A range of sensors are available to quantify the physical constraints for roots, but penetrometers of similar dimensions to a root and with a relieved shaft to limit friction between the shaft and the soil are best able to described the condition of the soil matrix for root proliferation. To penetrate the soil matrix a root requires both to expand the cavity it is to occupy and to overcome the soil-root friction. While cavity expansion is determined solely by the soil, the soil-root friction involves both the plant and the soil. This paper will start at the scale of an individual root tip elongating into the soil matrix, consider how the physical environment changes that elongation, and the consequences of soil variability in space and time for the individual root. Using the understanding of the individual root-soil interaction it will draw inference for larger scales, comment on how the understanding informs sustainable soil management and finally emphasise the need to deploy plant genetics and soil management together to improve long-term productivity.